A representação da mulher em O Círculo de Jafar Panahi: o Irã, o Islã e o cinema (1979-2001) - Amaral, Aline Moreira do (2015)
This dissertation examines the representation of women in the film The Circle , the Iranian director Jafar Panahi, reaching the so-called new Iranian cinema , and explore the boundaries of cinematic art of social intervention, its articulation with the censorship and the Islam in post- revolutionary Iran processes. From the Cultural History seeks to answer the following questions: How the Iranian Revolution has shaped your cinema? What is the role of women in his works of art? As Jafar Panahi represented the woman in The Circle ? What are your influences? I analyze these issues from the historian's point of view, using the filmic document , which approach have several possibilities became a rich working tool , capable of providing multiple interpretations and thoughts